Effects of TEDA Doping on The Adsorption Properties of Activated Carbon as The Filling Material of Iodine Sampler Filter on The KLK06 CR004 System in G.A. Siwabessy Multipurpose Reactor (RSG – GAS) - Cahyani Nelti Ulan; Vieska Rofianissa; Diene Noor Haerani; Nazly Kurniawan (Green Engineering Society, 2022)
The performance of KLK06 CR004 as the iodine sampler system is certainly related with the specification, also with the adsorption properties and capacity of the filter filling material, which is applied on that system. A certain Activated Carbon material is applied as the filling material for the filter part of KLK06 CR004, for the purpose of radioactive iodine sampling from the released air through the RSG – GAS stack. The characterization of the activated carbon for KLK06 CR004, with and without TEDA doping, has been carried out to develop as a candidate for the iodine sampler system. The material used in this research was The KLK06 CR004 activated carbon and The KLK06 CR004- TEDA doping with various composition of TEDA. The surface morphology of the activated carbon was investigated by Scanning Electron Microscope (SEM). Moreover, the qualitative and quantitative analysis of the activated carbon composition was also carried out in this research, by occupying the Energy Dispersive Spectroscopy (EDS). The adsorption surface area and particle size sample were analyzed by the Particle Size Analyzer (PSA) and Brunauer, Emmett, and Teller (BET).